Akselerasi Pembangunan Manusia Melalui Pendekatan Pendidikan Berbasis Kawasan (Studi Kasus di Dinas Pendidikan Kota Mojokerto) - Hermawan, Romy (JPAP: Jurnal Penelitian Administrasi Publik, 2018)
The study examine the challenge of Indonesia education is how to build human resourse in a compete with other nations in the world. The acceleration of human development not only the government responsibility, but also must be involve all stakeholders becomes the starting point in answering the challenges. Furthermore, in the study used theoretical basis of thuman resource management in educational perspective, research methodology usede qualitative method. This study concludes that area-based education in which community involvement and the harmonious creation relationships could be accelerate of human development. Â  Keyword: Acceleration, Human Development, Area-based Education